Answer:
[tex]m=-\frac{\sqrt3}{2}\ and\ m=\frac{\sqrt3}{2}[/tex]
Step-by-step explanation:
Given:
The equation given to solve is:
[tex]4m^2=3[/tex]
First, we divide both sides by 4. This gives,
[tex]\frac{4m^2}{4}=\frac{3}{4}\\\\m^2=\frac{3}{4}[/tex]
Now, we take square root on both sides. This gives,
[tex]\sqrt{m^2}=\pm\sqrt{\frac{3}{4}}[/tex]
We know that from the definition of square root function that:
[tex]\sqrt{x^2}=x[/tex]
[tex]\sqrt{\frac{x}{y}}=\frac{\sqrt{x}}{\sqrt{y}}[/tex]
Therefore,
[tex]\sqrt{m^2}=m[/tex]
[tex]\sqrt{\frac{3}{4}}=\frac{\sqrt{3}}{\sqrt{4}}=\frac{\sqrt3}{2}[/tex]
[tex]m=\pm\frac{\sqrt3}{2}[/tex]
Hence, two values of 'm' are possible. They are:
[tex]m=-\frac{\sqrt3}{2}\ and\ m=\frac{\sqrt3}{2}[/tex]